The Effects of Blue and Far Red Light on Rhythmic Leaflet Movements in Samanea and Albizzia - Satter, Ruth L. (1981)
The opening of excised Samanea saman pulvini is promoted by prolonged blue or far-red irradiation. Far-red effects are attributed partially but not completely to lowering of the Pfr level. Two hours of continuous or pulsed blue light or pulsed far-red light (total dosage = 2.2 × 10(18) quanta per square centimeter in all cases) also phase shifts the rhythm in Samanea while two hours of continuous blue light phase shifts the rhythm in the related plant Albizzia julibrissin. The same pigments appear to regulate opening and rhythmic phase shifting. The blue light-induced phase response curve has smaller advance and delay peaks and differs in shape from the curve induced by brief red light pulses absorbed by phytochrome. The blue absorbing pigment has not been identified, but it does not appear to be phytochrome acting in a photoreversible mode.